Revision Patella Tendon Repair With Hamstring Tendon Autograft Augmentation Following Failed Inferior Pole Patella Fracture Open Reduction and Internal Fixation. (August 2022) - Lowe, Dylan T.; Jazrawi, Laith M.; Egol, Kenneth A.
Summary: A 46-year-old man presents with left knee bucking 3 months after open reduction and internal fixation of a left knee inferior pole patella fracture. Radiograph and magnetic resonance imaging evaluation reveal displacement and comminution of the inferior pole of the patella confirming failure of the repair. The purpose of this video is to demonstrate the surgical management of failed inferior pole patella fractures using suture anchors for repair of the patella tendon and augmentation with ipsilateral autologous hamstring grafts.